Le Comité de l'Exposition Française à Copenhague en 1888 - Jasiński, Feliks Stanisław (1862-1901) (1888)
An etching by Felix Jasiński after the painting by P.S. Krøyer for the Gazette des Beaux-Arts, a French art review. The etching depicts members of the committee that organized the French Art Exhibition in Copenhagen in 1888.
Keywords: Committees; Art, French--Exhibitions